An Econometric Testing for The Application of CAPM in Damascus Stock Exchange (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study mainly aimed to test the validity of the Capital Asset Pricing Model (CAPM) in the Damascus Stock Exchange.The researcher tested CAPM by (Fama & MacBeth, 1973) approach with daily observations for the period from 1/1/2016 to 31/12/2023.The researcher used a portfolio of eight listed companies in the Damascus Stock Exchange.After we have done the descriptive tests on the research variables (Normal distribution – Unit Root test – Autocorrelation and Partial Autocorrelation test), the researcher used ARDL model to test CAPM.The study showed that CAPM invalid for application in the Damascus Stock Exchange, in spite of the model was significant in the first regression.We can say that CAPM - ARDL (4,4) was the best representative of the relationship between the excess return of market portfolio (DERm) and the excess return of managed portfolio (DERp).